SISTEM PAKAR MENGIDENTIFIKASI PENYAKIT ALAT REPRODUKSI MANUSIA MENGGUNAKAN METODE FORWARD CHAINING - Marwan Hakim (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2020)
Reproductive health is a state of mental health, physical and social welfare as a whole in all related to the systems and functions and processes and not just conditions that are free from disease and disability and are formed based on legal marriage, able to meet the proper spiritual and material needs, devoted to God Almighty, spiritual have a harmonious, harmonious, balanced relationship between family members and between family and society and the environment. Reproductive health includes three components, namely: ability, success, and safety. Expert sys tem is the right answer to the above problems because the expert system is a system designed to be able to imitate the expertise of an expert or expert in answering questions and solving a problem. Problem-solving is given to users through dialogue with them so that helps someone who is not an expert in answering questions, solving problems and making decisions that are usually done by an expert. The method used in knowledge representation is forward chaining. The results provide the possibility of venereal disease experienced by the user, the diagnosis in this system is done by the user filling out complaints or symptoms experienced when using this system. The results of the design will be made using the Delphi 7 Programming Language because it can create application programs that match the user-friendly appearance.